Utilization of TiungSAT-1 Data for Coastal Current Studies - Marghany , Maged (Astronautic Technology (M) Sdn. Bhd., 2003)
This study proposes a method for utilizing TiungSAT-1 data for coastal current studies. The Hopfield neural network has been used to model surface current movements. The study shows that the surface currents vectors range from 0.7 m/s to 1.4 m/s. It can be concluded that TiungSAT-1 data could be used for the detection of surface currents based on the intensity gradient variations that can be detected from the energy equation motion of neuron.